2010
DOI: 10.1016/j.mvr.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Collagen matrix physical properties modulate endothelial colony forming cell-derived vessels in vivo

Abstract: Developing tissue engineering approaches to generate functional vascular networks is important for improving treatments of peripheral and cardiovascular disease. Endothelial colony forming cells (ECFCs) are an endothelial progenitor cell (EPC) population defined by high proliferative potential and an ability to vascularize collagen-based matrices in vivo. Little is known regarding how physical properties of the local cell microenvironment guide vessel formation following EPC transplantation. In vitro evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 55 publications
10
126
1
Order By: Relevance
“…5Ai). Analyzing the human blood vessels, we found that they increased in size around the wound area during the proliferation period (days 5-7), then they regressed (days [11][12][13][14] and were further stabilized late in remodeling period (day 21), whereas the majority of microvessels (i.e., with a vessel area less than 200 m 2 ) remained (Fig. 5Aii).…”
Section: Vasculature Characteristics In the Treated Woundsmentioning
confidence: 93%
See 3 more Smart Citations
“…5Ai). Analyzing the human blood vessels, we found that they increased in size around the wound area during the proliferation period (days 5-7), then they regressed (days [11][12][13][14] and were further stabilized late in remodeling period (day 21), whereas the majority of microvessels (i.e., with a vessel area less than 200 m 2 ) remained (Fig. 5Aii).…”
Section: Vasculature Characteristics In the Treated Woundsmentioning
confidence: 93%
“…Through the transitions from inflammation to proliferation (days 5-7), approximately 28.21 Ϯ 4.57% of human vessels were covered by mouse SMCs. This percentage increased through the transitions from inflammation to proliferation (days [11][12][13][14], reaching 79.35 Ϯ 6. 51% at the late remodeling stage (day 21; Fig.…”
Section: Vasculature Characteristics In the Treated Woundsmentioning
confidence: 97%
See 2 more Smart Citations
“…72 Insufficient vascular network formation and maintenance drives many of these clinical disorders including diabetes, arthritis, atherosclerosis, and peripheral artery disease. 20,35 Local tissue ischemia resultant of insufficient blood flow is a potent stimulus for recruitment of progenitor blood forming cells including endothelial progenitor cells (EPCs). 63 EPCs are pivotal to maintaining vascular homeostasis and repair from injury.…”
Section: Introductionmentioning
confidence: 99%